(3EjVGM GdeSGdc aj TQM JSgjd GHf eGdcs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
"(3HGH efY GdUQa(B" (3gPG eKd ef bhdge HGH eG Hg UQa heG dG jUQa s
(3BNQgG (B:s
(3hgfG CJeeJ aj TQMj cJGHg GdebGd hChVMJ ajg GdCTcGd ced GdSaQ GdSGHY s
(3HgG JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs